Believe me when I say green!: Heterogeneous expectations and climate policy uncertainty - Emanuele Campiglio; Francesco Lamperti; Roberta Terranova (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
We develop a dynamic model where heterogeneous firms take investment decisions depending on their beliefs on future carbon prices. A policy-maker announces a forward-looking carbon price schedule but can decide to default on its plans if perceived transition risks are high. We show that weak policy commitment, especially when combined with ambitious mitigation announcements, can trap the economy into a vicious circle of credibility loss, carbon-intensive investments and increasing risk perceptions, ultimately leading to a failure of the transition. The presence of behavioural frictions and heterogeneity - both in capital investment choices and in the assessment of the policy-maker's credibility - has strong non-linear effects on the transition dynamics and the emergence of 'high-carbon traps'. We identify analytical conditions leading to a successful transition and provide a numerical application for the EU economy.
Keywords: C63; D84; E71; Q54; Q58; 330; Beliefs; behavioural macroeconomics; credibility; investment decision-making; heterogeneous expectations; low-carbon transition; policy uncertainty